Factors associated with successful outcome of infertility threatment at Hospital Raja Perempuan Zainab II - Zakaria, Siti Aisyah (2015)
Infertility is defined as the inability to conceive after a year of regular unprotected intercourse. Different treatment modalities are available to treat infertility ranging from simple, non-invasive oral agent such as clomiphene citrate to invasive procedure such as assisted reproductive technology (ART). The objective of this cross-sectional study was to determine the factors associated with the successful outcome of infertility treatment at Hospital Raja Perempuan Zainab II. Out of 429 cases, only 117 cases that fulfilled the inclusion creiteria were included. A retrospective record review was done using a checklist proforma consisting of sociodemography (age, ethnicity, education level and employment status), female variables (menstrual history, infertility history, sexual history, medical and surgical history, investigations, causes and treatment), male variables (smoking status, medical and surgical history, seminal fluid analysis, the last treatment method and its outcome ( success or failure). The successful outcome of treatment was categorised into intrauterine pregnancy, abortion or extrauterine pregnancy. The end outcome for intrauterine pregnancy was assessed in terms of mode of delivery (SVD or LSCS) and the fetal outcome (singleton or multiple births and gestational age). The descriptive methods and multiple logistic regression were applied to answer the objectives and hypotheses of this study. The overall successful rate post infertility treatment was 20.5% (95% CI: 16.8%, 24.2%) which resulted in thirteen intrauterine pregnancies, ten abortions and one extrauterine pregnancy. All thirteen pregnancies resulted in singleton babies, seven were delivered via SVD and six delivered via LSCS for precious pregnancy (two cases), fetal distress (2 cases) and one case of placenta praevia. Two of the babies were prematured, and the rest were delivered at term. Analysis from logistic regression showed that age of menarche (adj OR= 1.59,95% CI: 1.05, 2.42, p-value= 0.030) was the only significant factor affecting the successful outcome of infertility treatment when adjusted for age of men and women, BMI, duration of infertility, smoking, sperm characteristics (sperm count, percentage of progressive motility and normal morphology) and treatment options. The proportion of women with successful outcome post infertility treatment was almost similar to other studies and the odds of having a successful outcome are much higher in women with late age of menarche. Keywords: Infertility, intrauterine pregnancy, extrauterine pregnancy, abortion, age of menarche.